Otter trawling on the M/L A. Bros - Flores, Bonifacio G. (College of Fisheries, University of the Philippines, 1951)
Hinigaran has one of the best and clean fishing ground that I have seen in both north and south of Negros Occidental. The ground for fishing is very level that any experienced master fisherman could fish without any danger of destroying or entangling the net. Hinigaran has also a big river for any fishing boat to shelter during typhoon. Besides its river it is also the nearest place to an island named Guiwanon, the safest place to shelter for all fishing boat in that areas and that is why most of the experience master fisherman in this place even without any knowledge pertaining to map reading and navigation are still successful in their operation. It has an area of 24 square miles of fishing ground. In this area abundant marketable kind of fish are found such as the croakers, the small and big kind of slip-mouth, sarmullete, snappers, hairtail fish, flat-fish, cavalla, ray fish, crabs, and shrimps. In this place different kind of fishing gear are also used, such as the Baling-lawod (Tuck seine), Baling sinsoro (Drag seine), Basnig, fish trap, bill net, and also the cast net. The most successful among the fishing gear in this area is the newly introduced gear in the Philippines and have undergone the best and profitable changes by the Philippine Institute of Fisheries Technologies. The Philippines owed its progress to those men who have studied for many years the technique of fishing.